Generation Z's Efforts to Seek Peace: Alternative Narratives of Religious Moderation on Social Media - Eko Nur Wibowo; Okta Nurul Hidayati (Jurnal Al-Hikmah, 2023)
News and content regarding intolerance and radicalism still heavily color the social media world to this day. Cases of burning houses of worship, conflicts between religious communities, and discrimination against minorities are issues that seriously threaten peace. Therefore, alternative narratives of peace are needed to counter this narrative of intolerance. This study aims to examine alternative narratives regarding religious moderation carried out by the Literate Generation community. This research is a qualitative study with content analysis to examine how literate generations build alternative narratives on social media. For primary data obtained from the Literate Generation community with the activities it does. Secondary data from several books and scientific articles related to this research The researcher argues that Generation Literate uses social media as an alternative space to counter intolerance and radicalism. The results of the study show that the literate generation tries to build alternative narratives of peace from local religious values and community traditions.